Yahoo Web Search

  1. Sort by

  1. ...have ln(e^5) = k*2 + C. So we get ln(e^5) is 5, and 5 = 2*k + C. With y(5) = e^2, we get 2 = 5*k + C. Solving the 2 ...

    2 Answers · Science & Mathematics · 24/07/2016

  2. ... coefficient can be calculated as follows: a₀ = (k C 0) = k! / (0! k!) a₁ = (k C 1) = k! / (1! (k-1)!) a₂ = (k C...

    6 Answers · Science & Mathematics · 10/09/2011

  3. ...when there are no zeros b^2 - 4ac < 0 b = -4 a = k c= k (-4)^2 - 4(k)(k) < 0 k^2 > -4 For what number...

    1 Answers · Science & Mathematics · 26/02/2014

  4. ... its equation. For a plane equation in the form a(x-h) + b(y-k) + c(z-m) = 0 the normal vector is n = <a, b, c>. So...

    2 Answers · Science & Mathematics · 27/05/2010

  5. ...fit the defining Pascal's Triangle property: C(m,k) + C(m,k-1) = C(m+1,k) [0 < k <= m].  ...

    1 Answers · Science & Mathematics · 09/02/2020

  6. ...x)) / g(x) > 0 k (x + 3) (x − 4) / c > 0 This is true when k/c > 0 So general solution is: g(x) = c f(x) = k (x + 3) (x − 4...

    1 Answers · Science & Mathematics · 23/01/2018

  7. ...prime, we may conclude that p|m. Writing m = cp for some integer c, we get (cp)^k = c^k * p^k = p * n^k ==> n^k = c^k * p^(k-1). Since k > 1, we have...

    1 Answers · Science & Mathematics · 17/10/2009

  8. ...a+d, b+e, c+f) = T((a,b,c) + (d,e,f)), and k T(a, b, c) = k(c, b, a) = (kc, kb, ka) = T(ka, kb, kc) = T(k(a,b,c)), as required...

    1 Answers · Science & Mathematics · 19/06/2013

  9. ... when the probability of success is p is: (p^k)*[(1-p)^(n-k)]*[C(n,k)] (Note, tossing a coin is always a Bernoulli...

    2 Answers · Science & Mathematics · 08/08/2009

  10. ... and bars" along with inclusion-exclusion, # of ways = sum (-1)^k*C(24,k)*C(38-3k,23), k = 0 to 4 = 2252099280<------- # of ...

    2 Answers · Science & Mathematics · 03/12/2013

  1. Try asking your question on Yahoo Answers